Frameworks for Measuring Factors Associated With Healthcare Providers' Performance: A Scoping Review - Khalid Alkhurayji; Saja A. Alrayes; Arwa Alumran (Journal of Evaluation in Clinical Practice, 2026)
ABSTRACT Rationale Healthcare providers are influenced by several factors that affect their performance. However, no such work has been presented to organise or clarify this growing body of literature. Aim and Objectives This study aimed to identify frameworks for measuring factors affecting healthcare providers' performance. Methods This review adheres to the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis extensions for Scoping Reviews (PRISMA‐ScR). This review was guided by the Population, Concept, and Context framework recommended by the Joanna Briggs Institute (JBI). Searches were conducted in several databases and search engines, including PubMed, Web of Science, and Google Scholar. We included research articles of any design. A standardised data sheet was used for data extraction by each reviewer. The data extracted from the studies were related to the details of frameworks (name, country of origin, dimensions, indicator used, and setting of framework). The analysis of this review included variables from the framework details using ranges, medians, and counts, as appropriate. Furthermore, various interpretations of the results were presented in narrative form. Results We found 17 frameworks for measuring HCPP in terms of domains, subdomains, indicators, and depth of detail. Asia accounted for the majority of framework origins (70%). Most frameworks were published around 2020 (88.23%). The domains of the frameworks varied from 2 to 8, with a median score of 5. The findings were synthesised into 8‐categories covering aspects related to feedback, work environment, motivation, performance, well‐being, organisation, work‐life interface, and personal attributes. Conclusion The results of this review provide useful resources for the government, health institutes, and hospitals to inform them of the factors that affect the HCPP—specifically, choosing a framework that is systematically relevant to their institutions' contexts and settings.